C++ rush: interactive game for novices in learning basic computer language - Shaiful Nizam, Muhammad Salman Hakim; Rosmani, Arifah Fasha (Universiti Teknologi MARA, Kedah, 2023)
C++ is one of the fundamental, easy-to-learn programming languages that aid in understanding the fundamentals of all types of programming. Since the fundamentals of C++ have been mastered, migrating to other programming languages would be simple for someone with a solid grasp of the language. This project aims to design and develop an educational, interactive programming game. Using a questionnaire, another objective of this project is to assess the usability of the developed programming game. The methodology used for this project is Agile Model because iterative development is one of its components. The six phases of the Agile methodology are requirements, design, development, testing, deployment, and review. With 30 participants, usability testing was conducted for this study. The vast majority of individuals concur that gamification can transform a difficult and complex topic into an extremely enjoyable one. This project has ultimately enabled the user to learn C++ effectively. Future works may incorporate a wider variety of programming languages.